EFEKTIVITAS Pseudomonas sp. BOT4 DALAM MENDEGRADASI MINYAK JELANTAH MENGGUNAKAN SUMBER NITROGEN NATRIUM NITRAT DAN YEAST EXTRACT - Harfan, Donatus Tia; Rousdy, Diah Wulandari; Kurniatuhadi, Rikhsan (Jurnal Protobiont, 2019)
Jelantah is the residual waste of cooking oil. The disposal of untreated waste directly into the environment has the potential to promote damage such as water channels clogging and water body pollution. Form of waste treatment such as biodegradation can be done using potential bacteria such as Pseudomonas spp. which has been known for being effectively in decomposing organic waste. This study aimed to observe the ability ofÂ Pseudomonas sp. BOT4 in degrading jelantah with different nitrogen sources i.e. NaNO3 and yeast extract. This study was carried out from August to October 2018. The used cooking oil samples were homemade with deep frying method and the isolate samples were collected from used cooking oil-contaminated sewer water. Split plot design was used with time of incubation as main plots and nitrogen sources as subplots. The parameters observed were cell density and degraded oil weight. The results obtained stated that nitrogen sources of NaNO3 and yeast extract given optimum effect on cell density of Pseudomonas sp. BOT4 on day three each with OD600 value of 1,361 and 2,300. Nevertheless both nitrogen sources did not really give real effect on final weight of degraded oil, each with weight of 1,28 g dan 1,09 g.